A survey of multi-locus methods for analysis of large SNP datasets - Heidema, A. Geert (Henry Stewart Talks, 2007)
Statistical challenges in genetic association studies, Selection features of multi-locus methods and their strengths and weaknesses, A multi-step approach to analyze large numbers of SNPs, Application to a real case-control dataset
Archived at 2021/02/25